Characterization of dry bean genotypes (Phaseolus vulgaris) for resistance to Thrips palmi (Thysanoptera: Thripidae) - DÍAZ-M., JOHN; CARDONA-M., CÉSAR; BUENO, JUAN MIGUEL (Revista Colombiana de Entomología, 2003)
To identify sources of resistance to Thrips palmi Karny in dry beans (Phaseo/us vulgaris L.), three field trials were conducted in Pradera (Cauca Valley, Colombia) under heavy natural infestation. In the first trial, 38 genotypes were characterized for resistance to T. palmi in a completely randomized block design. In the other two trials, nine genotypes were used in a split-plot design. In one case, the main plot was fertilization level: while in the other, chemical protection was the main plot. Variation in T. pa/mi attack was detected in the genotypes tested. Thrip populations showed an aggregate pattern of distribution and had a significant effect on damage levels to plants. Damage .negatively affected reproductive adaptation and yield plants. Genotypes Brunca, BH 21134-5, EMP 486, BAT 477, FEB 115 y BH 21134-60 showed resistance to thrips in the experiments. Fertilization levels did not have an effect on resistance expression. Losses due to thrips damage ranged from 11,9% to 65,1 %. FEB 115, BH 21134-5, EMP 486, BH 21134-60 and Brunca were below the average susceptibility index of the experiment; genotypes with low susceptibility indexes may have a tolerance to damage and suffer lower losses. Further work is needed in order to elucidate the mechanisms of resistance to thrips in resistant genotypes.